2019
DOI: 10.1177/2041386619874870
|View full text |Cite
|
Sign up to set email alerts
|

How is safety climate formed? A meta-analysis of the antecedents of safety climate

Abstract: The purpose of this meta-analysis was to provide a comprehensive quantitative review of research to date on the antecedents of psychological and organizational safety climate. Building upon and expanding Zohar’s conceptual model, antecedents were organized into three broad categories: situational factors, interpersonal interactions, and personal factors. Data were gleaned from 136 primary studies to calculate effect sizes for 38 antecedents and the relative importance of each antecedent within the three catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 93 publications
1
25
0
Order By: Relevance
“…In general, we found a variety of different determinants. This cluster represented also determinants mentioned in other models, like job demands or job role [2,4]. Compared with topics and categories from Cornelissen et al [5], we found determinants for physical work environment, work characteristics, and workforce.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…In general, we found a variety of different determinants. This cluster represented also determinants mentioned in other models, like job demands or job role [2,4]. Compared with topics and categories from Cornelissen et al [5], we found determinants for physical work environment, work characteristics, and workforce.…”
Section: Discussionsupporting
confidence: 51%
“…The obtained overview and the comparison of determinants in different workplaces facilitate the identification of possible research requirements and implications, especially for hospital workplaces. We discuss the results for each of the seven clusters below, and compare our findings with antecedents identified in other models [2][3][4]. The topics addressed within this cluster were almost used equally by the studies at different workplaces (14/17 at hospital workplaces versus 21/27 at other workplaces).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations